2002
DOI: 10.1007/bf03000103
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes during neural deactivation in human brain: A positron emission tomography study of crossed cerebellar diaschisis

Abstract: The mechanism of crossed cerebellar diaschisis (CCD) is considered to be secondary hypoperfusion due to neural deactivation. To elucidate the hemodynamics during neural deactivation, the hemodynamics of CCD was investigated. The cerebral blood flow (CBF), cerebral blood volume (CBV), cerebral oxygen extraction fraction (OEF), cerebral metabolic rate of oxygen (CMRO2), and vascular responses to hypercapnia and acetazolamide stress for CCD were measured in 20 patients with cerebrovascular disease by positron emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…According to Poiseuille's law, the flow of blood through a vessel is proportional to the fourth power of the vessel diameter; blood volume is proportional to the square of the diameter. Thus, CBV ‫ס‬ cCBF 0.5 (c: constant) (Ito et al, 2001;Ito et al, 2002), which corresponds to the relation between CBF and CBV we observed.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…According to Poiseuille's law, the flow of blood through a vessel is proportional to the fourth power of the vessel diameter; blood volume is proportional to the square of the diameter. Thus, CBV ‫ס‬ cCBF 0.5 (c: constant) (Ito et al, 2001;Ito et al, 2002), which corresponds to the relation between CBF and CBV we observed.…”
Section: Discussionsupporting
confidence: 78%
“…This suggests that augmentation for CBF and CBV might be governed by a common microcirculatory mechanism during both neural activation and hypercapnia. We also used PET to investigate changes in both regional CBF and CBV in crossed cerebellar diaschisis (Ito et al, 2002), which can be considered neural deactivation (Gold and Lauritzen, 2002). The degree of decrease in CBF and CBV during neural deactivation was almost identical (approximately 20% decrease in both CBF and CBV), indicating no change in vascular blood velocity during neural deactivation Cerebral cortex CBF (%/mm Hg) 6.0 ± 2.6 −3.5 ± 0.6 CBV (%/mm Hg)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon, commonly known as diaschisis, has gained renewed interest from functional neuroimaging studies that revealed decreased metabolism and CBF in anatomically intact brain regions that were remote from a cerebral lesion (Baron et al, 1981;Martin and Raichle, 1983;Meneghetti et al, 1984;Price et al, 2001;Ito et al, 2002). We used decreased activity in the cortico-pontine-cerebellar projections to study the relationship between Purkinje cell spiking activity and CBF in the cerebellar cortex under conditions of deactivation (Fig.…”
Section: Deactivationmentioning
confidence: 99%